2021
DOI: 10.1038/s41598-021-94511-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index in pregnancy and mental disorders in adult offspring: a record linkage study in Aberdeen, Scotland

Abstract: Maternal obesity in pregnancy predicts offspring psychopathology risk in childhood but it remains unclear whether maternal obesity or underweight associate with adult offspring mental disorders. We examined longitudinally whether maternal body mass index (BMI) in pregnancy predicted mental disorders in her offspring and whether the associations differed by offspring birth year among 68,571 mother–child dyads of Aberdeen Maternity and Neonatal Databank, Scotland. The offspring were born 1950–1999. Maternal BMI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Follow‐up of men and women born in Helsinki in the 1930s and 40 s demonstrated that women whose mothers were of higher BMI were at greater risk of developing type 2 diabetes as adults 80 . In the same way, record linkage of 118,201 Aberdeen births (1950–2011) to the Scottish diabetes register revealed that offspring of overweight (OR = 1.39, 95% CI = 1.06–1.83) and obese (OR = 3.8, 95% CI = 2.33–5.06) mothers were at markedly elevated risk of type 2 diabetes 84 . There is also evidence that maternal obesity increases the risk of type 1 diabetes as among more than 1.26 million Swedish children born between 1992 and 2004, obesity in pregnancy predicted a type 1 diabetes diagnosis (OR = 1.33, 95% CI = 1.2–1.48) 85 .…”
Section: Maternal Obesity and The Programming Of Diseasementioning
confidence: 90%
See 1 more Smart Citation
“…Follow‐up of men and women born in Helsinki in the 1930s and 40 s demonstrated that women whose mothers were of higher BMI were at greater risk of developing type 2 diabetes as adults 80 . In the same way, record linkage of 118,201 Aberdeen births (1950–2011) to the Scottish diabetes register revealed that offspring of overweight (OR = 1.39, 95% CI = 1.06–1.83) and obese (OR = 3.8, 95% CI = 2.33–5.06) mothers were at markedly elevated risk of type 2 diabetes 84 . There is also evidence that maternal obesity increases the risk of type 1 diabetes as among more than 1.26 million Swedish children born between 1992 and 2004, obesity in pregnancy predicted a type 1 diabetes diagnosis (OR = 1.33, 95% CI = 1.2–1.48) 85 .…”
Section: Maternal Obesity and The Programming Of Diseasementioning
confidence: 90%
“…80 In the same way, record linkage of 118,201 Aberdeen births (1950-2011) to the Scottish diabetes register revealed that offspring of overweight (OR = 1.39, 95% CI = 1.06-1.83) and obese (OR = 3.8, 95% CI = 2.33-5.06) mothers were at markedly elevated risk of type 2 diabetes. 84 There is also evidence that maternal obesity increases the risk of type 1 diabetes as among more than 1.26 million Swedish children born between 1992 and 2004, obesity in pregnancy predicted a type 1 diabetes diagnosis (OR = 1.33, 95% CI = 1.2-1.48). 85 Similarly, analysis of data relating to the births of children who were subsequently hospitalised with type-1 diabetes found that maternal BMI > 30 kg m -2 was a significant risk factor (OR = 1.29, 95% CI = 1.01-1.64).…”
Section: Maternal Obesity and The Programming Of Diseasementioning
confidence: 99%
“…These points notwithstanding, we would argue that our pregnancy data are robust, having been derived from routine data sets that have been used in numerous other studies of obstetrics [ 19 ]. Further, these data reflect a population cohort from two broad and representative areas of Scotland, combining urban and rural data, with relatively stable population characteristics [ 13 16 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified all women aged 15 -44 at any point between the years 2005 and 2013 inclusive, who had at least one record in the PsyCIS or NHSGr psychiatric data sets with an ICD-10 diagnosis (lifetime or within an episode of care) of non-affective psychotic disorder (F20-F29). These datasets record routine psychiatric data on all patients seen by the secondary community mental health teams for NHS GGC and NHSGr health board areas for an episode of care (inpatient and outpatient) and have been previously used in mental health data science studies [13][14][15][16]. We termed this study group the 'exposed' group.…”
Section: Study Populationmentioning
confidence: 99%
“…16 Furthermore, there is some indication that pregnancies complicated by maternal obesity result in lower fetal oxygenation, 17 increased placental weight and thickness, 17 and an altered metabolic environment, 18 factors that could adversely impact fetal neurodevelopment. Previous studies have investigated the role of gestational weight gain and maternal body mass index (BMI) on risk of offspring non-affective psychosis 19 and mood disorders, 20 but its role on BPD is unknown. Because the prevalence of obesity among women of reproductive age has reached epidemic proportions, 21 it is essential to investigate its potential role on the etiology of BPD.…”
mentioning
confidence: 99%